Technical Efficiency in the Secondary Medical Service Region - Ogawa, Hikaru; Kubo, Rikizo (Iryo To Shakai, 2005)
This paper uses Data Envelopment Analysis (DEA) to measure technical efficiency of the Secondary Medical Service Region in Japan. A regression model is also employed to examine what causes a region to provide inefficient medical service. Possible factors influencing the efficiency are population and space size, the number of medical staffs and beds, among others. Results highlight the significant effects of regional population and the space size on the technical efficiency.